2018
DOI: 10.1039/c7dt04490a
|View full text |Cite
|
Sign up to set email alerts
|

Rise of A-site columnar-ordered A2A′A′′B4O12 quadruple perovskites with intrinsic triple order

Abstract: A-site-ordered AA'BO quadruple perovskites (with twelve-fold coordinated A and square-planar coordinated A' sites) were discovered in 1967. Since then, there have been considerable research efforts to synthesize and characterize new members of such perovskites. These efforts have led to the discoveries of many interesting physical and chemical properties, such as inter-site charge transfer and disproportionation, giant dielectric constant, multiferroic properties, reentrant structural transitions and high cata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
72
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 44 publications
(75 citation statements)
references
References 50 publications
3
72
0
Order By: Relevance
“…As it was expected from the crystallographic considerations, Ga 3+ was not found at the square‐planar A′ site. Distribution of Ga 3+ occurs between the tetrahedral A′′ site and octahedral B site with the preferred occupation of the A′′ site (with about 2 : 1 (A′′ : B) ratio).…”
Section: Figuresupporting
confidence: 73%
See 4 more Smart Citations
“…As it was expected from the crystallographic considerations, Ga 3+ was not found at the square‐planar A′ site. Distribution of Ga 3+ occurs between the tetrahedral A′′ site and octahedral B site with the preferred occupation of the A′′ site (with about 2 : 1 (A′′ : B) ratio).…”
Section: Figuresupporting
confidence: 73%
“…On the other hand, specific heat and magnetic measurements showed that Dy 2 CuMnMn 4 O 12 shows three long‐range magnetic order transitions at T N3 =21 K, T N2 =125 K, and T N1 =160 K (Figure ). The intrinsic nature of the three phase transitions is further supported by the fact that all R 2 CuMnMn 4 O 12 (R=Dy−Lu and Y) exhibit similar magnetic properties and systematic changes of phase transition temperatures …”
Section: Figurementioning
confidence: 84%
See 3 more Smart Citations